Knowledge, Attitudes and Practices (KAP) related to COVID-19 among members of Kabale University (KAB) community: a pre-intervention study - G.B, Turyasingura; E.B, Maniple; Nshakira, N.N; H.E, Ainamani; M, Karungi; J, Murangira (Task Force on COVID-19 Standard Operating Procedures, 2021)
COVID-19 is a highly infectious acute viral respiratory tract infection caused by a new coronavirus that was first detected in China in December 2019, after crossing from wild animals to humans. It spreads directly from person-to-person through salivary and nasal droplets expelled from an infected person during sneezing, coughing or talking that fall on the soft mucosa of a close by non-infected person (within one meter).